2017
DOI: 10.1016/j.omtm.2016.12.010
|View full text |Cite|
|
Sign up to set email alerts
|

Low-Dose Liver-Targeted Gene Therapy for Pompe Disease Enhances Therapeutic Efficacy of ERT via Immune Tolerance Induction

Abstract: Pompe disease results from acid α-glucosidase (GAA) deficiency, and enzyme replacement therapy (ERT) with recombinant human (rh) GAA has clinical benefits, although its limitations include the short half-life of GAA and the formation of antibody responses. The present study compared the efficacy of ERT against gene transfer with an adeno-associated viral (AAV) vector containing a liver-specific promoter. GAA knockout (KO) mice were administered either a weekly injection of rhGAA (20 mg/kg) or a single injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 42 publications
1
66
0
1
Order By: Relevance
“…The 1e11vg AAV GAA, 1e10vg AAV α-hCD63SC:GAA, and 1e11vg AAV α-hCD63SC:GAA groups had titers in the 10 4 -10 5 range, but these did not reach statistical significance versus control mice. These results agree with previous studies showing there is a serum level threshold that must be reached in order to induce tolerance to GAA 25 .…”
Section: Serum Titers Against Gaa Performed 3 Months After Infection supporting
confidence: 93%
“…The 1e11vg AAV GAA, 1e10vg AAV α-hCD63SC:GAA, and 1e11vg AAV α-hCD63SC:GAA groups had titers in the 10 4 -10 5 range, but these did not reach statistical significance versus control mice. These results agree with previous studies showing there is a serum level threshold that must be reached in order to induce tolerance to GAA 25 .…”
Section: Serum Titers Against Gaa Performed 3 Months After Infection supporting
confidence: 93%
“…The appeal of this approach, termed Bimmunomodulatory gene therapy^ [152], is twofold: it induces immune tolerance to GAA by activating regulatory T cells and can provide a stable expression of GAA in liver, thus converting liver into a depot for continuous secretion of GAA and cross-correction in distant organs. Preclinical studies have demonstrated that the secreted GAA is taken up by cardiac and skeletal muscles leading to glycogen reduction and improved muscle function [141,153]. A clinical trial which is scheduled to begin in the fall 2018 will explore the safety of liver-targeted gene therapy.…”
Section: Gene Therapy Strategiesmentioning
confidence: 99%
“…Gaa −/− mice on both the B6/129 and the pure 129SVE background lack GAA protein and GAA activity in the diaphragm [51][52][53][54][55]. As a result, the diaphragms of these Gaa −/− mice and the mice created by Bijvoet et al have significant glycogen accumulation as demonstrated by positive periodic acid-Schiff (PAS+) staining and mass spectrometry [39,40,51,52,[54][55][56][57][58][59][60]. Mass spectrometry provides evidence that Gaa −/− mice are born with glycogen accumulation in the diaphragm that progressively increases throughout life [56].…”
Section: Diaphragm and Phrenic Motor Neuron Pathologymentioning
confidence: 99%